Ráð Rétt Rúnar: reading the runes in Old English and Old Norse poetry - Birkett, T (2011)
Responding to the common plea in medieval inscriptions to ráð rétt rúnar, to ‘interpret the runes correctly’, this thesis provides a series of contextual readings of the runic topos in Anglo-Saxon and Old Norse poetry. The first chapter looks at the use of runes in the Old English riddles, examining the connections between material riddles and certain strategies used in the Exeter Book, and suggesting that runes were associated with a self-referential and engaged form of reading. Chapter 2 seeks a rationale for the use of runic abbreviations in Old English manuscripts, and proposes a poetic association with unlocking and revealing, as represented in Bede’s story of Imma. Chapter 3 considers the use of runes for their ornamental value, using 'Solomon and Saturn I' and the rune poems as examples of texts which foreground the visual and material dimension of writing, whilst Chapter 4 compares the depiction of runes in the heroic poems of the Poetic Edda with epigraphical evidence from the Migration Age, seeking to dispel the idea that they reflect historical practice. The final chapter looks at the construction of a mythology of writing in the Edda, exploring the ways in which myth reflects the social impacts of literacy. Taken together these approaches highlight the importance of reading the runes in poetry as literary constructs, the script often functioning as a form of metawriting, used to explore the parameters of literacy, and to draw attention to the process of writing itself.